High-elongation self-repairing polyurethane and preparation method thereof

By introducing imine bond chain extenders and trihydroxy crosslinkers into polyurethane to construct a three-dimensional network, the problem of high repair strength at high temperature or poor strength at low temperature of self-healing polyurethane materials was solved, self-healing and high elongation at room temperature were achieved, and the material can be repeatedly processed.

CN120647887AActive Publication Date: 2025-09-16ZHEJIANG UNIV +1

Patent Information

Application Number
CN202511165900.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-08-20
Publication Date
2025-09-16
Estimated Expiration
2045-08-20

AI Technical Summary

Technical Problem

Existing self-healing polyurethane materials have high repair temperatures when their mechanical strength is high, poor repair strength at low temperatures, and are complex to prepare, making them difficult to apply in practice.

Method used

A three-dimensional network structure is constructed by using a chain extender containing an imine bond and a trihydroxy crosslinker to prepare a high-elongation self-healing polyurethane, which achieves self-healing at room temperature.

Benefits of technology

It achieves excellent self-healing properties and high tensile elongation at room temperature. The material can be processed repeatedly after damage and maintains mechanical strength and toughness.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120647887A_ABST
    Figure CN120647887A_ABST
Patent Text Reader

Abstract

The invention discloses high-elongation self-repairing polyurethane and a preparation method thereof, and the preparation method comprises the following steps: step 1, in an inert gas atmosphere, carrying out catalytic reaction on polyol and isocyanate in a solvent to prepare a polyurethane prepolymer; step 2, adding an imine chain extender and a trihydroxy cross-linking agent into the reaction solution, and carrying out chain extension reaction to obtain self-repairing polyurethane; according to the invention, a chain extender containing dynamic reversible imine bonds is adopted to carry out chain extension on a polyurethane prepolymer, and meanwhile, a trihydroxy cross-linking agent is adopted to construct a three-dimensional network structure, so that cross-linked polyurethane containing imine dynamic bonds is prepared. The imine bond can be quickly exchanged at room temperature, and after the imine bond is broken, the imine bond is different from a traditional straight-chain molecule but a branched molecule, so that the flow processing is better, the molecular chain collision probability is higher, the tensile elongation is better, and the self-repairing property is excellent at room temperature; and the prepared cross-linked polyurethane can have excellent self-repairing performance at room temperature.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of polymer materials, and in particular to a high-elongation self-repairing polyurethane and a preparation method thereof. Background Art

[0002] Polyurethane is widely used in many fields such as coatings, adhesives, automobiles and construction. In these application scenarios, polyurethane will inevitably be subjected to mechanical, light or thermal stimulation during use, resulting in microcracks or wounds, affecting its mechanical properties and even causing material failure. Therefore, the preparation of polyurethane with self-healing function has become a research hotspot. In the prior art, dynamic covalent bonds are usually introduced into polyurethane to achieve the effect of self-healing, such as imine bonds, acylhydrazone bonds, disulfide bonds, borate bonds, DA reactions, etc. In addition, non-covalent bonds such as hydrogen bonds, ionic bonds, host-guest interactions, and metal ligands are also often introduced into polyurethane. Under the stimulation of light, heat, microwaves and other conditions, the polyurethane chain segments flow, and cracks and damage are repaired.

[0003] CN115124688A discloses a polyurethane damping material containing dynamic disulfide and imine bonds and its preparation method. This damping material reacts with cystine, an alcohol compound, and thionyl chloride to introduce dynamic disulfide bonds and intramolecular hydrogen bonds into the system. This is then reacted with an aldehyde compound to synthesize a polyurethane chain extender containing both dynamic disulfide and imine bonds. Alternatively, a polyurethane chain extender containing both dynamic disulfide and imine bonds is synthesized using diaminodiphenyl disulfide and an aldehyde compound in anhydrous ethanol. Finally, this is reacted with a polyurethane prepolymer to produce a polyurethane damping material containing both dynamic disulfide and imine bonds. This polyurethane damping material utilizes the reversible nature of dynamic covalent bonds to increase energy dissipation. It exhibits a wide damping temperature range, high damping performance, and excellent mechanical and self-repairing properties, making it suitable for a wide range of applications.

[0004] CN119661809A discloses a self-repairing, water-resistant polyurethane elastomer containing an imine bond, and is used in humidity sensors. However, these chain extenders all contain two imine bonds with high dynamic activity. If these two imine bonds are broken at the same time, small molecules will be lost and the mechanical properties and self-repair properties of the material will be affected, causing the material to fail. CN116355173A discloses a self-repairing, degradable bio-based polyurethane containing a single imine bond, which has excellent repeatability. However, the self-repair rate, effect, and toughness are not as good as those of a chain extender system containing two imine bonds. In addition, the synthesis and preparation of the chain extender containing a single imine bond are relatively complicated and difficult to apply in practice. It can be seen that if the coating needs to achieve a better self-repair effect, it needs to be heat treated separately.

[0005] However, the self-healing polyurethanes currently prepared are materials with relatively high mechanical strength, but the required repair temperature is often relatively high. The mechanical strength of materials with low repair temperature is poor, and the preparation is complex, making it difficult to apply in practice. Summary of the Invention

[0006] In response to the existing technical defects, this discovery synthesized a chain extender containing an imine bond, which was then used to extend the polyurethane prepolymer. At the same time, a trihydroxy crosslinker was used to construct a three-dimensional network structure to prepare a cross-linked polyurethane containing imine dynamic bonds, which showed better tensile elongation and excellent self-repairing properties at room temperature, enabling the prepared cross-linked polyurethane to have excellent self-repairing properties at room temperature.

[0007] To achieve the above object, the technical solution adopted by the present invention is: A method for preparing high-strength self-repairing polyurethane comprises the following steps: Step 1: Under an inert gas atmosphere, polyol and isocyanate are catalytically reacted in a solvent to prepare a polyurethane prepolymer; Step 2, adding an imine chain extender and a trihydroxy crosslinker to the reaction solution to obtain a self-repairing polyurethane through a chain extension reaction; The structure of the imine chain extender is as follows: .

[0008] In the present invention, a chain extender containing a dynamically reversible imine bond is used to extend the polyurethane prepolymer, while a trihydroxy crosslinker is used to construct a three-dimensional network structure, thereby preparing a cross-linked polyurethane containing dynamic imine bonds. The presence of a biphenyl ring structure in the chain extender can more effectively improve the strength of the product. After the prepared sample was cut and repaired at 30°C for 6 hours, the tensile strength reached 98% of the uncut value, demonstrating excellent self-healing capabilities. Because the imine bond can be rapidly exchanged at room temperature and, after breaking, the imine bond does not form a traditional linear molecule but a branched molecule, it has better flow processing, a greater probability of molecular chain collision, and exhibits better tensile elongation. As well as excellent self-healing properties at room temperature, the prepared cross-linked polyurethane can possess excellent self-healing properties at room temperature.

[0009] The preparation of the imine chain extender comprises the following steps: adding anhydrous sodium sulfate and p-4-aminophenol to a p-hydroxybenzaldehyde solution, filtering after reaction, and drying the precipitate after removing the solvent from the filtrate to obtain the imine chain extender.

[0010]

[0011] The molar ratio of p-hydroxybenzaldehyde to anhydrous sodium sulfate is 1:0.1-0.12; The molar ratio of p-hydroxybenzaldehyde to 4-aminophenol is 1:0.8-1.2; The reaction temperature is 30-50°C and the reaction time is 3-8 hours. The preparation conditions of the chain extender are mild and the process is simple, which creates favorable conditions for industrial promotion.

[0012] The polyol includes at least one of polytetramethylene glycol, polycaprolactone glycol, and polybutylene adipate; The isocyanate includes one of isophorone diisocyanate, 4,4-diisocyanate dicyclohexylmethane, and diphenylmethane diisocyanate; The catalyst used in step 1 includes one or more of dibutyltin dilaurate, bismuth neodecanoate, and stannous octoate; the catalyst mass is 20-500 ppm of the polyol; The solvent used in step 1 includes one or more of toluene, ethylbenzene, and xylene.

[0013] In step 1, the molar ratio of polyol to isocyanate is 1:1.95-1:2.05, the reaction temperature of polyol and isocyanate is 30-60° C., and the reaction time is 3-5 hours. Preferably, the polyol is dehydrated before use.

[0014] The trihydroxy cross-linking agent includes one or more of glycerol and triethanolamine; The molar ratio of the total molar amount of hydroxyl groups of the imine chain extender and the trihydroxy crosslinking agent to the isocyanate groups in the polyurethane prepolymer is 1.0:1-1.3:1.

[0015] The molar ratio of the imine chain extender to the trihydroxy crosslinker is 4:1-1:1; The chain extension reaction in step 2 is carried out under an inert gas atmosphere, with a reaction temperature of 30-80° C. and a reaction time of 2-10 h.

[0016] The present invention also provides a polyurethane produced according to the preparation method. The preparation method is simple, the reaction conditions are mild, and the resulting product can achieve self-repair at room temperature without the need for additional conditions. Furthermore, the polyurethane of the present invention has excellent reprocessability. After being damaged and then repeatedly processed, the resulting polyurethane material maintains substantially consistent mechanical strength and has improved toughness.

[0017] Compared with the prior art, the present invention has the following beneficial effects: (1) In the present invention, a chain extender containing a benzene ring and an imine bond and a trihydroxy crosslinker are used to extend the polyurethane prepolymer to obtain a polyurethane material with excellent self-repairing properties and tensile toughness, which can achieve a self-repairing effect at room temperature.

[0018] (2) The polyurethane of the present invention also has excellent reprocessability. The polyurethane material obtained by repeated processing after destruction basically maintains the same mechanical strength, and the toughness is also improved. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 This is the NMR spectrum of the imine chain extender obtained in Preparation Example 1.

[0020] Figure 2 This is the infrared spectrum of the imine chain extender obtained in Preparation Example 1.

[0021] Figure 3 The infrared spectra of the polyurethanes synthesized in Example 1 and Comparative Example 1 are shown.

[0022] Figure 4 The stress-strain curves of the polyurethane samples of Examples and Comparative Examples are shown in FIG.

[0023] Figure 5 This is a comparison chart of the self-repair of the polyurethane samples of Example 1 and Comparative Example 1.

[0024] Figure 6 The stress-strain curves of comparative example 1 repaired at different times at room temperature.

[0025] Figure 7 The stress-strain curves of Example 1 repaired at different times at room temperature.

[0026] Figure 8 This is a comparison chart of repeated processing of the polyurethane samples of Example 1 and Comparative Example 1.

[0027] Figure 9 This is the stress-strain curve of the polyurethane sample of Example 1 after multiple repeated processing. DETAILED DESCRIPTION

[0028] In order to make the purpose, technical solutions and advantages of the present invention clearer, the present invention is further described in detail below in conjunction with embodiment. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention. Those skilled in the art will make modifications or equivalent substitutions based on understanding the technical solution of the present invention, without departing from the spirit and scope of the technical solution of the present invention, and all should be encompassed within the protection scope of the present invention.

[0029] The raw materials used in the following specific embodiments are all purchased from the market.

[0030] Preparation Example 1 p-Hydroxybenzaldehyde (12.21 g) was added to a 100 mL three-necked flask, followed by dissolution in 40 mL of anhydrous ethanol. After heating to 40°C, anhydrous sodium sulfate (1.42 g) was added, followed by p-4-aminophenol (10.91 g). The solution turned a beautiful golden yellow. After the reaction continued for 5 hours, the solution was filtered to separate the inorganic salts. The solution was then distilled under reduced pressure to remove most of the anhydrous ethanol, and then dried under vacuum at 60°C for 12 hours to obtain the imine chain extender as a yellow solid with a calculated yield of 90%.

[0031] Infrared measurements were performed on a Thermo Nicolet 6700 infrared spectrometer. The sample was coated on a KBr plate and dried under an infrared lamp before measurement. The measurement temperature was room temperature (25°C) and the scanning range was 4000-500 cm. -1 , scanning frequency is 32 s -1 , with a resolution of 4 cm -1 .

[0032] The structure of the product was analyzed using nuclear magnetic resonance (1H-NMR Agilent 600MHz DD2). The substance to be analyzed was dissolved in deuterated dimethyl sulfoxide (DMSO-D6) at room temperature and then tested.

[0033] like Figure 1 As shown, it can be seen from the nuclear magnetic resonance that there is a peak of hydrogen on the imine bond (-CH=N-) at 8.44 ppm, the double peak at 7.72~7.76 ppm is the peak of hydrogen close to the aldehyde group on the benzene ring of the original p-hydroxybenzaldehyde, the peak at 7.10~7.12 ppm is the peak of hydrogen close to the N atom on the benzene ring, the peak at 6.83~6.87 ppm is the peak close to the hydroxyl group on the benzene ring of the original p-hydroxybenzaldehyde, and the peak at 6.76~6.79 ppm is the peak of hydrogen close to the hydroxyl group on the benzene ring of the original p-hydroxybenzamine.

[0034] like Figure 2 As shown, p-hydroxybenzaldehyde is located at 1700 cm -1 The characteristic absorption peak of aldehyde group at 1517cm -1 、1580 cm -1 and 1496 cm -1 The C=C absorption peak of the benzene ring appears at 1602 cm -1 A new imine bond (-CH=N-) absorption peak appears at 3370 cm -1 and 734 cm -1The characteristic absorption peak of -OH appears at , indicating that the imine chain extender has been successfully synthesized. Its -OH can react with isocyanate (-NCO) to extend the chain, and the imine bond can provide self-healing properties for the prepared polyurethane.

[0035] As shown in Table 1, the reaction conditions and the amount of anhydrous sodium sulfate were changed to obtain Preparation Examples 1-5, and the yields were calculated.

[0036] Table 1 Reaction temperature, amount of anhydrous sodium sulfate added and yield of imine chain extender prepared in Preparation Example 1-5

[0037] Example 1 Step 1: A three-necked flask containing polytetrahydrofuran diol (PTMEG, Mn≈1000 g / mol, 10 g) was dehydrated under reduced pressure at 100°C for 1 hour. The temperature was then lowered to 70°C under high-purity nitrogen. Isophorone diisocyanate (4.45 g) and 30 mL of anhydrous toluene were added in a -NCO / -OH molar ratio of 2 / 1, followed by the addition of 20 ppm of the catalyst dibutyltin dilaurate (DBTDL). The reaction was continued under high-purity nitrogen for 3 hours, and the flask was then cooled to 40°C. The product was treated to obtain a prepolymer. In step 2, the -NCO content of the product from step 1 was titrated. Based on the -NCO content, an imine chain extender and a crosslinker, triethanolamine, were added in a 1:1 molar ratio (the total molar amount of hydroxyl groups in the chain extender and crosslinker being equal to the -NCO molar amount of the prepolymer). The reaction was continued. Stirring was stopped after the reactant gelled and the reaction was continued at 50°C for 6 hours to complete the reaction. Finally, the product was vacuum-dried at 80°C for 12 hours to obtain an imine dynamically crosslinked polyurethane (CPU-I). Different polyurethanes were obtained according to the raw material ratios shown in Table 2.

[0038] Table 2 Molar ratio of raw materials for preparing self-repairing polyurethane in Examples 1-5

[0039] Comparative Example 1 Step 1: Remove water from a three-necked flask containing polytetrahydrofuran (PTMEG, Mn≈1000 g / mol, 10 g) under reduced pressure at 100°C for 1 hour. Then, under high-purity nitrogen, cool to 70°C. Add isophorone diisocyanate (4.45 g) and 30 mL of anhydrous toluene at a -NCO / -OH molar ratio of 2 / 1, followed by 20 ppm of the catalyst dibutyltin dilaurate (DBTDL). After reacting for 3 hours under high-purity nitrogen, cool the flask to 40°C. In step 2, the -NCO content of the product from step 1 was titrated. Based on the -NCO content, a 1:1 molar ratio of butanediol (BDO) and crosslinker triethanolamine was added (the total molar weight of hydroxyl groups in the chain extender and crosslinker being equal to the -NCO molar weight of the prepolymer). The reaction was continued. Stirring was stopped after the reactants gelled, and the reaction was continued at 50°C for 6 hours to complete the reaction. Finally, the product was vacuum dried at 80°C for 12 hours to obtain a conventional crosslinked polyurethane (CPU-B).

[0040] like Figure 3 As shown, the cross-linked polyurethanes CPU-I and CPU-B generated by the addition of cross-linking agent and imine chain extender or BDO are located at 2258 cm -1 The characteristic absorption peak of -NCO at 1517 cm-1 completely disappeared, and the absorption peak at 1517 cm-1 appeared in the infrared spectrum of CPU-I. -1 A new benzene ring absorption peak appeared at 1602 cm -1 The absorption peak of imine bond (-CH=N-) was found at 400 nm, indicating that imine dynamic cross-linked polyurethane had been successfully synthesized.

[0041] The pressure and strain curves and mechanical data of Examples 1-4 and Comparative Example 1 are shown in Tables 3 and Figure 4 As shown, when more imine bonds are present, dynamic crosslinks allow polymer segments to slip and rearrange more easily when stressed, resulting in higher ductility. The reversible breakage and reorganization of dynamic crosslinks effectively dissipates energy and delays material fracture. More dynamic covalent crosslinks can reversibly break and reorganize under stress, effectively dissipating energy while maintaining network integrity, thereby increasing strength.

[0042] As can be seen from Example 1 and Comparative Example 1, the polyurethane prepared by the chain extension reaction using a chain extender containing an imine bond has rapidly exchanged imine bonds, resulting in its strength being lower than that of ordinary polyurethane; however, precisely because of the presence of rapidly exchanged dynamic bonds, chain segment rearrangement also occurs during the stretching process, resulting in the dynamically cross-linked polymer having a higher elongation at break, especially the lower the stretching rate, the longer the elongation at break.

[0043] Table 3 Mechanical properties of samples of Examples 1-4 and Comparative Example 1

[0044] Use a blade to cut the cross-linked polyurethane into obvious marks, such as Figure 5 As shown, scratch self-repair experiments were conducted on a polarizing microscope (ECLIPSE E600W POL) with a hot and cold stage. The sample was placed in air at a temperature of 30°C and a magnification of 100x to observe the scratch repair process. Example 1 could be repaired to a complete absence, while Comparative Example 1 could not be repaired.

[0045] The repair effect of the cross-linked polyurethane was further quantitatively characterized by a cutting-repair experiment. The synthesized cross-linked polyurethane Example 1 and Comparative Example 1 were cut into two halves with a blade, and then the samples were closely contacted again. After repairing for a specific time at 30°C, stress-strain tests were performed. The results are shown in FIG. Figure 6 and Figure 7 The repair rate is defined as the ratio of the tensile strength of the repaired sample to the tensile strength of the uncut sample.

[0046] from Figure 6 It can be seen that the comparative example 1 has basically no self-repairing performance, with only a repair rate of 21.6%, and it is almost unchanged over time, indicating that the comparative example 1 is only slightly bonded together due to the excellent bonding performance of polyurethane and cannot self-repair. Figure 7 As can be seen from the results, Example 1 has a very high repair efficiency, reaching a 44.9% repair rate after 0.5 hours and a 97.9% repair rate after 6 hours, essentially achieving self-repair. This result further demonstrates that the introduction of imine dynamic bonds can impart exceptional self-repairing properties to cross-linked polyurethanes.

[0047] To further test the repeatable processing performance, e.g. Figure 8 As shown in FIG, the sample after the tensile test was cut into small pieces with scissors at room temperature, and then the small pieces were placed in a stainless steel mold and pressed at 2 MPa and 90°C for 20 min, and then cooled to room temperature to obtain a repeatedly processed sample. It can be seen from the figure that Example 1 can be repeatedly processed, while Comparative Example 1 cannot be repeatedly processed. The samples obtained by repeated processing were also subjected to mechanical property tests, and the results are shown in FIG. Figure 9 and as shown in Table 4.

[0048] Table 4 Mechanical properties of the polyurethane sample of Example 1 after repeated processing

[0049] From Table 4 and Figure 9 It can be seen that after repeated processing, the Young's modulus and breaking strength of Example 1 decreased, while the elongation at break significantly increased. This is because during the hot pressing process, the polymer molecules can fully exchange and relax the internal stress as much as possible, resulting in a decrease in yield strength and an increase in elongation at break. In turn, the toughness of the material is improved. After repeated processing, the elongation at break and the breaking strength do not change much.

Claims

1. A method for preparing a high elongation self-repairing polyurethane, characterized in that: Including steps: Step 1: Under an inert gas atmosphere, polyol and isocyanate are catalytically reacted in a solvent to prepare a polyurethane prepolymer; Step 2, adding an imine chain extender and a trihydroxy crosslinker to the reaction solution to obtain a self-repairing polyurethane through a chain extension reaction; The structure of the imine chain extender is as follows: 。 2. The method for preparing a high-elongation self-repairing polyurethane according to claim 1, characterized in that: The preparation of the imine chain extender comprises the following steps: adding anhydrous sodium sulfate and p-4-aminophenol to a p-hydroxybenzaldehyde solution, filtering after reaction, and drying the precipitate after removing the solvent from the filtrate to obtain the imine chain extender.

3. The method for preparing a high-elongation self-repairing polyurethane according to claim 2, characterized in that: The molar ratio of p-hydroxybenzaldehyde to anhydrous sodium sulfate is 1:0.1-0.12; The molar ratio of p-hydroxybenzaldehyde to 4-aminophenol is 1:0.8-1.2; The reaction temperature is 30°C-50°C, and the reaction time is 3-8h.

4. The method for preparing a high-elongation self-repairing polyurethane according to claim 1, characterized in that: The polyol includes at least one of polytetramethylene glycol, polycaprolactone glycol, and polybutylene adipate; The isocyanate includes one of isophorone diisocyanate, 4,4-diisocyanate dicyclohexylmethane, and diphenylmethane diisocyanate; The catalyst used in step 1 includes one or more of dibutyltin dilaurate, bismuth neodecanoate, and stannous octoate; the catalyst mass is 20-500 ppm of the polyol; The solvent used in step 1 includes one or more of toluene, ethylbenzene, and xylene.

5. The method for preparing a high-elongation self-repairing polyurethane according to claim 1, characterized in that: In step 1, the molar ratio of polyol to isocyanate is 1:1.95-1:2.05, the reaction temperature of polyol and isocyanate is 30-60° C., and the reaction time is 3-5 hours.

6. The method for preparing a high-elongation self-repairing polyurethane according to claim 1, characterized in that: The trihydroxy cross-linking agent includes one or more of glycerol and triethanolamine.

7. The method for preparing a high-elongation self-repairing polyurethane according to claim 1, characterized in that: The molar ratio of the total molar amount of hydroxyl groups of the imine chain extender and the trihydroxy crosslinking agent to the isocyanate groups in the polyurethane prepolymer is 1.0:1-1.3:

1.

8. The method for preparing a high-elongation self-repairing polyurethane according to claim 1, characterized in that: The molar ratio of the imine chain extender to the cross-linking agent is 4:1-1:

1.

9. The method for preparing a high-elongation self-repairing polyurethane according to claim 1, characterized in that: The chain extension reaction in step 2 is carried out under an inert gas atmosphere, with a reaction temperature of 30-80° C. and a reaction time of 2-10 h.

10. The polyurethane prepared according to the preparation method according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Polyurethane damping material containing dynamic disulfide bonds and imine bonds and preparation method thereof

    CN115124688A

  • Self-repairing degradable bio-based polyurethane containing single imine bond and preparation method of self-repairing degradable bio-based polyurethane

    CN116355173A

  • Water-resistant self-repairing polyurethane elastomer, preparation method thereof and application of polyurethane elastomer in humidity sensor

    CN119661809A

  • Liquid crystalline polyurethane elastomer and method for producing same

    CN105829380A

  • Self-healing hyperbranched polyurethane with high mechanical strength as well as preparation method and application thereof

    CN113105608A

Cited By

  • An energetic self-healing functional polyurethane and a preparation method thereof

    CN122520882A